2024
DOI: 10.1038/s41598-024-60170-y
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of prothrombin time in Plasmodium falciparum and Plasmodium vivax infections with different levels of severity: a systematic review and meta-analysis

Suriyan Sukati,
Tirawat Wannatung,
Thitinat Duangchan
et al.

Abstract: Malaria infection leads to hematological abnormalities, including deranged prothrombin time (PT). Given the inconsistent findings regarding PT in malaria across different severities and between Plasmodium falciparum and P. vivax, this study aimed to synthesize available evidence on PT variations in clinical malaria. A systematic literature search was performed in PubMed, Embase, Scopus, Ovid, and Medline from 27 November 2021 to 2 March 2023 to obtain studies documenting PT in malaria. Study quality was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Recent research concluded that thrombocytopenia is an excellent diagnostic marker of malaria, with 86.3% specificity and 79.5% sensitivity [ 21 ]. The effect of malaria severity on coagulation parameters is well documented [ 22 , 23 ]. A high parasitaemia load leads to anomalies in the synthesising and secretion of coagulation factors and their inhibitors and hepatic microcirculation blockage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research concluded that thrombocytopenia is an excellent diagnostic marker of malaria, with 86.3% specificity and 79.5% sensitivity [ 21 ]. The effect of malaria severity on coagulation parameters is well documented [ 22 , 23 ]. A high parasitaemia load leads to anomalies in the synthesising and secretion of coagulation factors and their inhibitors and hepatic microcirculation blockage.…”
Section: Discussionmentioning
confidence: 99%